Synthesis of N4-aryl-β-D-glucopyranosylcytosines: a methodology study - Mamais, Michael; Kouloumoundra, Virginia; Smyrli, Eugenia; Grammatopoulos, Paschalis; Chrysina, Evangelia D.; Gimisis, Thanasis (Tetrahedron Lett., 2015)
© 2015 Elsevier Ltd. All rights reserved.A number of leaving groups, including arylsulfonates, triazoles, 3-nitrotriazoles, and tetrazoles, have been studied for the substitution reaction by aryl and alkyl amines at the 4-position of $β$-D-glucopyranosyluracils. Examination of the stability, ease of purification and reactivity in the substitution reaction led to a number of optimized conditions with the most convenient involving substitution of triazole derivatives under microwave conditions in the presence of silica gel. Under these conditions, a number of N4-aryl-substituted $β$-D-glucopyranosylcytosines were prepared as potential inhibitors of glycogen phosphorylase, a molecular target for type-2 diabetes mellitus.
Keywords: Microwaves; N4; [Arylamines